Identification of bacterial diversity from an oil-spill contaminated marine environment in Tanjung Karang, Selangor, Malaysia - Faizul Hadry Nordin, Noor; Feisal Merican, Amir (Malaysian Journal of Science, 2001)
Bacteria were isolated from crude oil contaminated muddy beach by using the liquid enrichment culture method. Two different types of samples have been taken which are in solidified form and in liquid form (from seawater as oil slick). Colony and cell morphological studies as well as physiological and biochemical studies using classical biochemical test were used to identify some of the isolates as bacteria from the genera Acinetobacter, Pseudomonas, Moraxella, Neisseria and Staphylococcus.